2019
DOI: 10.2174/2210303109666190118162157
|View full text |Cite
|
Sign up to set email alerts
|

Casuarina equisetifoliaExtract Loaded Phytosomes: Optimization, Characterization andIn vivoEvaluation of Antidiabetic and Antihyperlipidemic Activities in Wistar Rats

Abstract: Background: Herbal extracts have brilliant in-vitro activity but less in-vivo action in light of their macromolecular size and poor lipid solubility bringing about poor absorption and low bioavailability. These issues can be corrected by designing novel drug delivery systems. Phytosomes provide better absorption and bioavailability when compared to conventional herbal extract. Objective: This paper deals with the preparation, optimization and characterization of Phytosome of plant extract and in vivo assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…An optimized formulation was selected on the premise of predetermined criteria like minimum particle size, maximum entrapment efficiency, high drug content, and good in vitro drug release. [16,17]…”
Section: Selection Of Optimized Batch Of Phytosomesmentioning
confidence: 99%
“…An optimized formulation was selected on the premise of predetermined criteria like minimum particle size, maximum entrapment efficiency, high drug content, and good in vitro drug release. [16,17]…”
Section: Selection Of Optimized Batch Of Phytosomesmentioning
confidence: 99%
“…Typically, polyphenolic compounds are present as an integral part of phospholipid membrane in phytosomes and display better pharmacological performance compared to liposomes containing polyphenolic constituents in their inner cavity [ 16 ]. Rani et al [ 17 ] has reported that the phytosome of Casuarina equisetifolia extract containing chrysin improved antidiabetic and antihyperlipidemic activities in Wistar rats.…”
Section: Introductionmentioning
confidence: 99%